(untitled) (International Journal of Food and Nutritional Sciences, 2022)
We define Acharya Index AIλ(G) of a connected graph with respect to D-distance as the sum of the D-distance between all pair of vertices of degree d, which is inspired by research on the Acharya index of connected graphs, its chemical implications, and its mathematical traits. In this study, we calculated the AI(G) for standard graphs.